Parrotfishes (Teleostei: Labridae: Scarini) of the Socotra Archipelago: Diversity and distributional biogeography, including a range extension of Scarus zufar Randall & Hoover, 1995 - Zajonz, Uwe; Bogorodsky, Sergey V.; Saeed, Fouad K.n.; Al-Deed, Moteah S.; Lavergne, Edouard (Zootaxa, 2023)
An updated account of the diversity of parrotfishes from the Socotra Archipelago is provided. Fourteen species are positively recorded based on underwater observations, photography and collections, including confirmations of three species which were previously only tentatively recorded: Scarus falcipinnis (Playfair, 1868), Scarus scaber Valenciennes, 1840 and Scarus tricolor Bleeker, 1847. The distribution of Scarus zufar Randall & Hoover, 1995, previously known only from coastal waters of southern Oman, Pakistan and Bangladesh, is extended to the Archipelago, with Abd al-Kuri Island representing the westernmost edge of its known range. Visual records of three additional species are yet to be documented. With 14–17 species the Archipelago approximates the modal richness range of 15–18 species for Arabian ecoregions. A species account, accompanied by photographs, provides distinctive characters, distribution details in the Arabian region, and general remarks for each species. The distributional biogeography of the family pertinent to the Socotra Archipelago and the Arabian region is analysed in the context of the Western Indian Ocean. Three main Arabian units are identified: A ‘Red Sea unit’ spans the combined Red Sea ecoregions and the western Gulf of Aden; a ‘Socotra unit’ covers south-eastern Arabia including the Archipelago, the eastern Gulf of Aden and southern Oman; and a ‘Gulf unit’ combines the Arabian/Persian Gulf, the Gulf of Oman, and putatively central Oman. These units form a discrete “pan-Arabian” cluster within the wider Western Indian Ocean. The ‘Socotra unit’ resembles more strongly the ‘Gulf unit’ than the ‘Red Sea unit’. Parrotfishes thus contrast overall distributional patterns of reef fishes in Arabia.